2015
DOI: 10.1016/s1470-2045(15)70137-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of neoadjuvant bevacizumab added to docetaxel followed by fluorouracil, epirubicin, and cyclophosphamide, for women with HER2-negative early breast cancer (ARTemis): an open-label, randomised, phase 3 trial

Abstract: Cancer Research UK, Roche, Sanofi-Aventis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 30 publications
6
106
0
Order By: Relevance
“…More patients achieved pCR in the combination-therapy arm compared to the chemotherapy alone arm, in line with reports from previous studies (6,7,10,11). A significant benefit of adding bevacizumab was observed in the ER-positive subgroup consistent with the larger NSAPB-B40 trial (11), in contradiction to the GeparQuinto trial, where the ERnegative tumors were found to benefit from bevacizumab (10), and the CALGB40603 study, including patients with a low ER expression, or triple negative tumors (6).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…More patients achieved pCR in the combination-therapy arm compared to the chemotherapy alone arm, in line with reports from previous studies (6,7,10,11). A significant benefit of adding bevacizumab was observed in the ER-positive subgroup consistent with the larger NSAPB-B40 trial (11), in contradiction to the GeparQuinto trial, where the ERnegative tumors were found to benefit from bevacizumab (10), and the CALGB40603 study, including patients with a low ER expression, or triple negative tumors (6).…”
Section: Discussionsupporting
confidence: 82%
“…Blocking VEGF by bevacizumab, a monoclonal antibody, has been proposed to cause inhibition of neovascularization, regression of existing immature micro-vessels, and normalization of abnormal vasculature (4,5); this has consequences for the flux of oxygen, nutrients, metabolites and therapeutic agents, ultimately preventing tumor growth and resulting in tumor shrinkage. However, addition of bevacizumab to standard chemotherapy in unselected breast cancer patients has resulted only in a modest increase in response rate and progression free survival (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies report significant increases in the percentage of patients with no detectable residual diseasereferred to as pathologic complete response (pCR)-with the addition of bevacizumab to neoadjuvant chemotherapy in human epidermal growth factor receptor 2 (HER2)-negative BC. The GeparQuinto, the CALGB 40603, and the ARTemis trials demonstrated a significant increase in pCR with the addition of bevacizumab in patients with triple-negative BC (TNBC) (6)(7)(8). However, the National Surgical Adjuvant Breast and Bowel Project Significance Emerging evidence indicates patients who benefit from antiangiogenic therapies have improved vessel function.…”
mentioning
confidence: 99%
“…These results suggest that ARHGAP17 mediated by VEGF–NRP1 interaction partly contributed to DFS in HR(−) BCs. As shown in Supporting Information Table S10, the association between HR status and bevacizumab treatment efficacy in clinical trials has been inconsistent 9, 41, 42, 43, 44, 45, 46, 47. Our findings demonstrated that there are bevacizumab‐independent VEGF signals in HR(−) BC tumors.…”
Section: Discussionmentioning
confidence: 62%